Storage Debt: Applying the Theoretical Model of ʻTechnical Debt' to the Management of Museum Storage. - Tomás-Hernandez, Ana (Museum International, 2021)
Numerous recent studies have identified critical issues with a high percentage of museum storage facilities around the world. The problems detected in such studies are usually solved with ambitious renovation projects, or through the reorganisation of existing resources. This article, drawing from the example of five Spain-based museums, explores the new concept of 'Storage Debt'. Storage debt refers to the cumulative processes and factors that generate the critical conditions mentioned above, which are quite costly to reverse and which adversely affect museums' activities at multiple levels. The storage debt concept arose from the theoretical framework of 'technical debt' (coined in the software development industry) and applied to the museum field. The former concept refers to actions and decisions that solve a need in the short term, but that in the future generate contexts that make core activities challenging and whose resolution involves extra efforts and resources. This article brings the theory of debt to the museum discipline by defining the concept, characterising the debt that accumulates in the context of museum storage and identifying strategies that museums can apply to solve the problem within the context of their collections. Making the accumulation of storage debt visible raises awareness around the additional cost that it implies for museum operations, but also around its potential effects on the value of collections. In this sense, the concept can facilitate communication with museum partners unfamiliar with the more technical aspects of museum management, such as patrons or sponsors. Likewise, when paired with risk analysis, the concept of storage debt makes it possible to shift away from a crisis model toward a predictive model: one that is more institutionally viable and sustainable.